P11.06 LYMPHOMATOSIS CEREBRI: A RARE FORM OF PRIMARY CENTRAL NERVOUS SYSTEM LYMPHOMA - Izquierdo, C. (Oxford University Press, 2014)
INTRODUCTION: Primary central nervous system lymphomas (PCNSL) are a unusual form of non-Hodgkin lymphoma, restricted to the neuroaxis and eyes.In most cases magnetic resonance imaging (MRI) disclose single or multiples lesions with mass effect and contrast enhancement. Rarely,PCNSL may occur as a diffuse non enhanced infiltrative lesion, a variant called Lymphomatosis Cerebri (LC).LC can present with a progressive course and diffuse white matter abnormalities on MRI what includes a wide differential diagnosis, becoming a diagnostic challenge. OBJECTIVE: To present the detailed characteristics of 4 patients who were diagnosed of LC at our centers and analyze the results of a systematic review of this entity. MATERIAL AND METHODS: A systematic literature search was carried out using Pubmed an ISI Web of knowledge to 1 February 2014.The search also included reference lists of papers identified. Demographic, clinical, histological, cerebrospinal fluid (CSF), MRI and therapeutic data were extracted. Patients with nodular enhancement at first MRI or concurrent systemic lymphoma were excluded. RESULTS: 28 patients from literature and 4 new patients were included. The median age was 58.5 years old (29-80).53.1% of patients were women. Only 1 was not inmunocompetent.62.5% out of patients presented with a Karnofsky Performance Status (KPS) <70. Most common presenting symptoms were cognition impairment (59.4%) and behavioral changes (50%).18.8% developed seizures. First MRI showed patchy enhancement in 33.3% of patients. Nearly half of patients (48.6%) had infratentorial and supratentorial infiltration. Both hemispheres were infiltrated in 96.8% of cases. Spinal cord was affected in 2 patients. CSF results were normal in 18.8% of patients. The median time to diagnosis was 150 days (30-900). Diagnosis was postmortem in 35.5% of patients. Treatments administered included: only corticoids (34.4%), chemotherapy and/or radiotherapy (46.9%). Median overall survival was 248 days (80-1890). According treatment, median survival was 3, 6.9, 44.3 months in no treated, only receiving corticoids and treated with chemotherapy/radiotherapy patients, respectively. One third of all patients were alive 1 year after the onset of the illness. Univariate analysis revealed that age ≥ 59 years (p = 0.029), KPS < 70 (p = 0.01), hypoglycorrhachia (p < 0.001) and lack of chemotherapy and/or radiotherapy treatment (p = 0.02) were associated with worst prognosis.The multivariate analysis demonstrated that KPS was the only independent prognostic factor for survival (HR: 0.65; ( CI95%:0.004-0.946); p = 0.045). CONCLUSION: LC is frequently misdiagnosed and associated with a considerable diagnostic delay that could explain the low performance status of patients at diagnosis. Despite to the fact that some patients can respond to the oncologic treatment, KPS is the only independent prognostic factor identified.